Prescribing Appropriate Medicines to Older Adults : A Finnish Experience with the Web-Based Meds75+ Database - Jyrkkä, Johanna; Paulamäki, Jasmin; Hartikainen, Sirpa; Ahonen, Jouni; Antikainen, Riitta; Jauhonen, Hanna-Mari; Jämsen, Esa; Kössi, Anniina; Laurila, Jouko; Roitto, Hanna-Maria; Söderling, Riikka; Tiihonen, Miia; et al. (Adis, 2025)
The Finnish web-based Meds75+ database supports rational, safe and appropriate prescribing to older adults in primary care. This article describes the content and updating process of Meds75+ and demonstrates its applicability in everyday clinical practice. Meds75+ contains a classification (A-D) and recommendation texts for 450-500 drug substances when used in the treatment of older adults aged 75 years or older. The content of Meds75+ is continually updated. Each assessment of a drug substance begins with a structured collection of available information and research evidence. After that, an interdisciplinary expert panel discusses the classification and recommendation using a consensus method. A rolling 3-year updating cycle guarantees that all drug substances are reviewed regularly. Most drug substances are classified as class A (41%) (suitable, e.g. bisoprolol) or as class C (37%) (suitable with specific precautions, e.g. ibuprofen). One-fifth (20%) of the substances are in class D (avoid use, e.g. diazepam). Most commonly, older adults have purchased substances affecting the alimentary tract and metabolism (17%), the nervous system (16%) and the cardiovascular system (15%). In Finland, the proportion of older adults using class D substances (37%) has not changed between the years 2019 and 2022. Meds75+ has potential to support safer and more effective use of medications for older adults, since it offers up-to-date information on drug substances for healthcare professionals.